Effect of ZnO nanoparticles filler concentration on the properties of PEO-ENR50-LiCF3SO3 solid polymeric electrolyte - Noor S.A.M.; Ahmad A.; Talib I.A.; Rahman M.Y.A. (2023)
A solid polymer electrolyte comprising blend of poly(ethylene oxide) and 50% epoxidized natural rubber (ENR50) as a polymer host, LiCF3SO3 as a salt and nanoparticle ZnO as an inorganic filler was prepared by solution-casting technique. The effect of filler on the electrolyte properties was characterized and analysed. FESEM analysis showed that the filler was well distributed in the polymer matrix, while the effective interaction between the salt and the polymer host was reduced by the addition of filler. As evidenced by FTIR analysis, which showed the formation of triplet peak at C-O-C stretching region. Ionic conductivity was found to decrease from 1. 4 10-4 Scm-1 to 2. 5 10-6 Scm-1 upon the addition of filler, due to the blocking effect of filler into the electrolyte conduction pathways. The temperature dependence on the electrolyte conductivity obeys Arrhenius rule in two temperature regions. 2011 Springer-Verlag.